Association between hallucinations and sensory processing difficulties in children and adolescents - Nishiura, Sayaka; Miyawaki, Dai; Hirai, Kaoru; Sukigara, Ayaka; Kakishita, Yui; Inoue, Koki (Frontiers in Psychiatry, 2024)
Introduction: Hallucinations are serious symptoms that can lead to high levels of distress, functional impairment, and increased risk of suicide in both adults and children. However, their etiology and treatment remain unclear. Hallucinations and sensory processing difficulties (SPDs) are associated with various psychiatric disorders, including mood, anxiety, and post-traumatic stress disorder. This study aimed to investigate the potential association between hallucinations and SPDs in a pediatric population. Methods: We conducted a cross-sectional study with 335 children aged 6–18 years who visited the child psychiatry outpatient clinic at Osaka Metropolitan University Hospital between April 2020 and March 2023 and continued treatment for at least three months. After excluding those with intellectual disabilities or uncontrolled epilepsy, 304 participants were included in the analyses. The presence of hallucinations was assessed through interviews with the children and their parents. SPDs were evaluated using the Short Sensory Profile. Binomial logistic regression analysis was conducted to assess the association between hallucinations and SPDs, adjusting for age, sex, autism spectrum disorder, socioeconomic difficulties (low-income, single-parent households), and the presence of mood and anxiety disorders. Results: Hallucinations were present in 64 children (21%). Logistic regression analysis showed a significant positive association between SPDs and hallucinations, even after adjusting for age, sex, autism spectrum disorder, socioeconomic difficulties, and the presence of mood and anxiety disorders (odds ratio, 1.02; 95% CI, 1.008–1.036; p = 0.002). Conclusion: The results of this study suggest a potential association between hallucinations and SPDs in pediatric patients. Further prospective studies are needed to explore the causal relationship between these factors and determine whether interventions for SPDs can alleviate hallucinations in children.